2020
DOI: 10.1007/s11882-020-00954-0
|View full text |Cite
|
Sign up to set email alerts
|

Antigen 5 Allergens of Hymenoptera Venoms and Their Role in Diagnosis and Therapy of Venom Allergy

Abstract: Purpose of Review Stings of Hymenoptera of the superfamily Vespoidea such as yellow jackets, paper wasps or stinging ants are common triggers for severe and even fatal allergic reactions. Antigen 5 allergens are potent allergens in the majority of these venoms with major importance for diagnosis and therapy. Reviewed here are the characteristics of antigen 5 allergens, their role in component-resolved diagnostics as well as current limitations of the available diagnostics for proper therapeutic decisions. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 81 publications
0
43
0
Order By: Relevance
“…Antigen 5 (Ag5) proteins are listed as important major venom allergens for most allergy-relevant Vespoidea species [34,56]. Although Ag5 allergens are one of the most abundant proteins in most Vespoidea venoms, their function within the venoms remains largely unclear.…”
Section: Antigens 5 (Ves V 5 and Pol D 5)mentioning
confidence: 99%
See 1 more Smart Citation
“…Antigen 5 (Ag5) proteins are listed as important major venom allergens for most allergy-relevant Vespoidea species [34,56]. Although Ag5 allergens are one of the most abundant proteins in most Vespoidea venoms, their function within the venoms remains largely unclear.…”
Section: Antigens 5 (Ves V 5 and Pol D 5)mentioning
confidence: 99%
“…Sensitization to the second commercially available Ag5, Pol d 5 from PDV, in primary PDV-sensitized patients is difficult to assess since a substantial percentage of the respective patient populations is DS to PDV and YJV with unknown primary sensitizer. Nevertheless, the available studies suggest that Ag5 proteins represent the most potent allergens in almost all studies allergy-eliciting Vespoidea species [56].…”
Section: Antigens 5 (Ves V 5 and Pol D 5)mentioning
confidence: 99%
“…PR-1 proteins are ubiquitous in plant species and it is suggested that PR-1 has a broad antimicrobial function. Antigens 5 are proteins of unknown function in Hymenoptera venoms with strong allergenic potency [ 85 ]. When we aligned the first CAP domain of contig 2455 with the Hymenoptera antigen 5 sequences (which have only one domain), we obtained a good match with about 35–40% identity ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“… Alignment of the first CAP domain of contig 2455 (Mp-CRISP) with selected sequences of hymenoptera antigen 5 allergens. The CAP signature motifs are shaded in grey and conserved residues that form the putative active site are shaded in cyan [ 85 ]. Cysteine residues that form disulphide bridges in Ag5 proteins are marked in red.…”
Section: Figurementioning
confidence: 99%
“…Antigens 5 are proteins of unknown function in Hymenoptera venoms with high allergenic potency. In addition to Phospholipase A1, antigen 5 represents one of the most important major venom allergens in almost all allergy-relevant Vespoidea species [6].…”
Section: Introductionmentioning
confidence: 99%